Initial-boundary-value Problem for a Degenerate Quasilinear Parabolic Equation of Order 2m (Journal of Partial Differential Equations, 1990)
In this paper we consider the initial-boundary value problem for the higher-order degenerate quasilinear parabolic equation \frac{&#8706u(x, t)}{&#8706t} + &#931_{|&#945|&#8804M}(-1)^{|&#945|}D^&#945A_&#945(x, t, &#948u, D^mu) = 0 Under some structural conditions for A_&#945(x, t, &#948u, D^mu), existence and uniqueness theorem are proved by applying variational operator theory and Gal&#235rkin method.